Digital Literacy As A Solution To Improve The Quality Of Indonesia's Human Resources - Harmoko, Danang Dwi (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2021)
The Indonesian literacy index in 2020 is still low, to be precise at 0.54. Even though literacy skills, especially in the digital field, are an important component in facing challenges in the future. Therefore, various efforts are needed to increase the national digital literacy index. This study aims to provide an overview of the importance of digital literacy education to improve the quality of human resources to face the demographic bonus in 2030-2040. This study used a qualitative descriptive method, while the data were taken from various literature sources, both print and online. The result of this research is that digital literacy education is very important for improving the quality of Indonesia's human resources. Individuals who have digital literacy will have certain characteristics, such as 1) the ability to use digital potential maximally, 2) digital resilience, 3) become positive and productive individuals, and 4) become part of the world community